(untitled) (Research, Society and Development, 2022)
Objective: To carry out an integrative review about the clinical manifestations and impact of the long COVID syndrome in adults. Methodology: This is a study with a qualitative approach, integrative review, whose article data collection was carried out by the “Publish or Perish” software, with a search with the title and keywords “long COVID” and “post COVID” and selected articles that have H-index, a citation metric. Results and Discussion: 3999 articles were searched, 567 with H-index and 29 selected for article. Grouped by themes: epidemiology of long COVID: most affected groups; risk factors or predictors; clinical manifestations; symptom progression; relationship between the severity of the acute condition and long-term COVID; specific situation after hospital discharge and socioeconomic impact. The study showed a higher prevalence in females, a higher age group, with a relevance of data for the persistence of symptoms, with many or specific symptoms at the beginning of the condition as a risk factor, whose most frequent clinical manifestations were fatigue, dyspnea and neuropsychological condition, with variable progression and significant impact on health and life. Conclusion: Due to the size of affected patients and the proportion of the long COVID syndrome presented in the studies, it is necessary to be able to identify the aspects related to long COVID and the impact on the quality of life and livelihood of individuals in order to encourage scientific production on the subject. of topics not yet well clarified and providing updates to health professionals.